EKSPLORASI LIMBAH MARMER TULUNGAGUNG SEBAGAI BAHAN BAKU PRODUK DEKORASI INTERIOR - Prasetyo, Yusro Defri; Nugraha, Adhi (Universitas Mercu Buana, 2024)
Marble is a superior natural resource in Tulungagung Regency, which is utilized for various types of crafts and building construction materials. Apart from all its benefits, marble processing also leaves waste that has an impact on the marble industry and the surrounding community. Marble shards, gravel, and powder are residues from marble waste. The purpose of this study is to create products made from marble waste to optimize material supplies. The design of this product can not only meet the demands of the community for environmentally friendly products but will also indirectly impact the sustainability of the marble industry in Tulungagung. By using a qualitative approach, this study uses design development and material exploration methods, all of which aim to make marble waste a raw material for product design. Through the experimental method applied to explore marble waste, its potential has been revealed as a new alternative for raw materials for making products in the marble industry. The exploration process uses marble waste, namely marble shards, gravel, and powder that have been sorted and other supporting materials such as water and white cement, to obtain the ideal formula in terms of strength, aesthetics, and ease of production. Challenges such as inconsistent material textures, varying hardening times also arise during the process, but instead open up opportunities for innovation in design approaches and production techniques. This research attempts to reduce waste while utilizing the unique characteristics of various types and proportions of marble waste. This collaborative effort with local craftsmen has resulted in interior decoration products, adding value to marble waste, strengthening the local economy, and maintaining the sustainability of the marble industry in Tulungagung.